Development of Android-Based 3D Building Augmented Reality Application at Jogja Student Islamic Boarding School 2 - Ramadhan, Muhamad Ali Nugroho; Waluyo, Anita Fira (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
Islamic boarding schools are pivotal in providing religious education for Muslims in Indonesia. Despite their widespread presence, detailed knowledge about these institutions, particularly their architectural design, remains limited. Prospective students and the public often rely on internet images for information, leading to a partial understanding of the physical structure of these schools. This study introduces an innovative solution through the development of an Augmented Reality (AR) mobile application specifically designed for the Jogja 2 Islamic Boarding School. Augmented Reality technology effectively integrates 2D and 3D virtual objects into a real-world environment, offering an immersive, real-time experience. By utilizing the waterfall methodology in its development, this application aims to provide an in-depth, three-dimensional exploration of the Jogja 2 boarding school's infrastructure. This tool is intended to assist potential students and interested individuals in gaining a comprehensive understanding of the school's architectural layout and design dynamically and interactively.